1996
DOI: 10.1111/j.1475-6765.1996.tb00667.x
|View full text |Cite
|
Sign up to set email alerts
|

The dissatisfied society: The roots of political change in Italy

Abstract: Since early 1990s in Italy there has been a major change in the party system. Some of the explanations that are often mentioned, such as corruption, the April 1993 referendum, the new electoral laws, or the secularization of the society and the economic crisis, are important aspects of a complex funnel of causality. Together, however, they do not satisfactorily explain the change. Thus, we identify an idiosyncratic factor, the chronic, widespread dissatisfaction, that existed since the end of the 1940s, and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
11

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(46 citation statements)
references
References 11 publications
0
35
0
11
Order By: Relevance
“…In fact, we can see that the ICC does not get much lower and that the amount of variance explained at the year level by model 2 is small. As has already been noted, the individual component of dissatisfaction in Italy seems to be marginal (Morlino and Tarchi 1996).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…In fact, we can see that the ICC does not get much lower and that the amount of variance explained at the year level by model 2 is small. As has already been noted, the individual component of dissatisfaction in Italy seems to be marginal (Morlino and Tarchi 1996).…”
Section: Resultsmentioning
confidence: 92%
“…Dissatisfaction with democracy in Italy also differs significantly from other southern European countries at least until the beginning of 2008, when the whole area experienced the beginning of one of the deepest economic crises in its recent history. Overall, the Italian pattern seems to resemble those of the new eastern democracies, indicating the low quality of outcome and performance achieved by the political system in Italy and the failure of decisions taken by political elites during the period (Memoli 2009;Morlino and Tarchi 1996). Nevertheless, it is worth mentioning that dissatisfaction has fluctuated over time and that it is possible to identify cycles that correspond to specific phases of democratisation of the Italian political system.…”
Section: Forty Years Of Political Discontent In Italymentioning
confidence: 89%
See 1 more Smart Citation
“…These traditional traits of Italian political culture, together with a very weak feeling of national identity in civic terms, entail constantly high levels of political distrust and discontent and are considered as the main explanatory factors, at social level, of the diffuse tolerance towards the generalised corruption (Davigo and Mannozzi, 2007), but also of the widespread feeling of social isolation and political alienation (Almond and Verba, 1989;Segatti, 2006). The latter points can be thus considered as general indicators of a failed process of modernisation of Italian politics, but also -at the same time -the main factors triggering political change in the given, specific political contexts of crisis (Morlino and Tarchi, 1996;Mutti, 2000).…”
Section: The Transformations and The Recurring Crises Of Italian Demomentioning
confidence: 99%
“…At the same time, there remain grounds for caution, since certain case studies suggest that economic performance, by itself, may provide only a poor fit to account for trends in political trust observed in many countries. Among post-industrial societies, for example, both Italy and Japan experienced rapid economic growth during the post-war era, although we have already observed that political disaffection in both countries remains pervasive and enduring (Morlino and Tarchi 1996;Pharr 2000). Moreover American confidence in government declined throughout the 1960s, despite the prosperous US economy during this decade (Lawrence 1997).…”
Section: Policy Performancementioning
confidence: 99%